A study of rbl gene in malaysian children with retinoblastoma: association of exon 18 mutation with clinical presentation - Tajuddin, Liza Sharmini Ahmad (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Background To date, there is no reports are available on RB I gene mutations in Malaysian children with retinoblastoma. The purpose of this study is to determine the presence of pocket B ElA domain mutations of RBI gene and their clinical presentation in Malaysian children with retinoblastoma (RB). Material and methods Children with RB from 2 main referral centers in Malaysia who fulfilled the inclusion criteria were enrolled into this study. Their clinical presentation were analyzed. Three mililitres of blood was taken for the genetic analysis from each patient. Mutations of exon 20 to 22 of RB I gene were identified by standard techniques of DNA extraction, PCR amplification, dHPLC and sequencing DNA. Results Fifty RB children (69 eyes) were recruited in this study. The most common presentation was leukocoria (65%) followed by strabismus (9%), proptosis (7%), orbital inflammation (10%), vitreous haemorhage (3%) and secondary glaucoma (3%). Majority presented at advanced stage. There was one mutation identified at the flanking region of intron 19 (substitution A~G). Conclusion: Leukocoria is the main clinical presentation in this study. Although strabismus, proptosis and orbital inflammation accounts about 26 % of the patients, it cannot be considered as rare presentation. One mutation was found in the flanking region ofintron 19.